Pelatihan Pengelolaan Sampah Rumah Tangga dengan Metode Komposting Takakura: Training on Household Waste Management using the Takakura Composting Method - Zrimurti Mappau; Fahrul Islam (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Indonesia produced 37.3% of household waste out of a total of 67.8 million tons of waste in 2020. Mamuju produces the average waste 1.6 tons of waste per day which is dominated by household waste. The training activity aimed to empower the community in the management of household waste with takakura composting methods. The target of community service activities were the mothers of farmer groups in Bambu Village, Mamuju District as many as 20 people. The PKM activity method uses lecture and demonstration methods. The stages of community service activities are started with counseling on household plastic waste management, counseling on household kitchen waste management, demonstrations and practices on household waste management with composting methods. All participants are very enthusiastic about participating in activities characterized by the presence of participants in all stages of packaging activities that are always on time and also the activeness of participants in composting practices. There is an increase in the number of participants with good knowledge about household plastic waste management from 20% to 85%. And also good knowledge of household kitchen waste management from 45% to 85%. At the end of the activity formed 2 houses that became a pilot house for making takakura compost. ABSTRAK Indonesia menghasilkan 37,3% sampah rumah tangga dari total 67,8 juta ton sampah pada tahun 2020. Kabupaten Mamuju rata-rata menghasilkan sampah 1,6 ton per hari yang didominasi oleh jenis sampah limbah rumah tangga. Pelatihan dalam kegiatan pengabdian ini bertujuan untuk memberdayakan masyarakat dalam pengelolaan sampah rumah tangga dengan metode komposting Takakura. Sasaran kegiatan pengabdian kepada masyarakat adalah ibu-ibu kelompok tani di Desa Bambu, Kecamatan Mamuju sebanyak 20 orang. Metode kegiatan PKM menggunakan metode ceramah dan demonstrasi. Tahapan kegiatan PKM dimulai dengan penyuluhan tentang pengelolaan sampah plastik rumah tangga, penyuluhan tentang pengelolaan sampah dapur rumah tangga, demonstrasi dan praktik tentang pengelolaan sampah rumah tangga dengan metode komposting. Semua peserta sangat antusias mengikuti kegiatan ditandai dengan kehadiran peserta dalam semua tahapan kegiatan pengabmas yang selalu tepat waktu dan juga keaktifan peserta dalam praktik pembuatan kompos. Terdapat peningkatan jumlah peserta dengan pengetahuan baik tentang pengelolaan sampah plastik rumah tangga dari 20% menjadi 85%. Dan juga pengetahuan baik tentang pengelolaan sampah dapur rumah tangga dari 45% menjadi 85%. Di akhir kegiatan terbentuk 2 rumah yang menjadi rumah percontohan pembuatan kompos takakura.